Parenting Patterns in the Formation of Children's Behavior (Case Study in Children with ADHD) - Minsih, Minsih (Universitas Muhammadiyah Surakarta, 2023)
Parents play a crucial role as the primary caregivers and educators of children, each employing their unique parenting style. This research aimed to elucidate the parenting patterns employed by parents in influencing the behavior of children with Attention Deficit Hyperactivity Disorder (ADHD). The study utilized a qualitative research method with a case study approach, focusing on children diagnosed with ADHD. The data collection process incorporated interviews, observations, and documentary studies. Rigorous data validation is achieved through source triangulation and technique triangulation. The interactive analysis model involves data reduction, presentation, and subsequent conclusion drawing. The research findings reveal that parents of children with ADHD adopt both permissive and authoritarian parenting patterns. Observable parenting behaviors include allowing excessive freedom, maintaining a constant belief in being right, and consistently acquiescing to the desires of the ADHD child. These parenting patterns contribute to the development of dependent behaviors in children, manifesting as an unwillingness to compromise, emotional instability, and involvement in actions detrimental to others.